A geophysical and geomorphological investigation of large-offset normal faulting in Beachlands, Auckland. Issue 1 (2nd January 2021) - Gasston, Caleb; Lindsay, Jan M.; Eccles, Jennifer D.; Brook, Martin; Hill, Matthew; Kenny, Jill
ABSTRACT: The identification and characterisation of faults in urban environments is important to inform seismic and landslide hazard, yet urban development often obscures geological and geomorphological evidence of fault traces. On the other hand, urban development also generates a wealth of borehole data, which, when combined with geophysical surveys, can enable a view into the subsurface. Here we combine geomorphological and geological mapping, gravity surveying, and 3D geological modelling to identify, map and characterise several faults in Beachlands, Auckland, some of which have large offsets. Our work has identified one new fault, the Motukaraka Fault, and confirmed the presence of two proposed faults, the Waikopua North and Te Puru faults. The Motukaraka and Waikopua North faults are both steeply dipping normal faults, which strike NNW and downthrow Mesozoic basement to the west. The Motukaraka Fault has an offset of 250 m (±100 m) and the Waikopua North Fault a combined offset of 240 m (±50 m) across two parallel fault segments. The Te Puru fault strikes northeast near the northern extent of the Waikopua Fault, and downthrows Mesozoic basement to the northwest by 60–100 m. Further investigations are required to determine whether these buried faults are active.